Synthesis, characterization and biological activity of platinum(II) complexes with a tetrapyrazole ligand. (14th December 2015) - Higuera-Padilla, Angel R.; Capote, Jorlis; Ortega, Dianela; Castro, William; Rodriguez-Cordero, Mildred; Coll, David; Hernández-Medina, Fernando; Fernández-Mestre, Mercedes; Urdanibia, Izaskun; Taylor, Peter; Rodriguez, Barbara; Karam, Arquímedes
Graphical abstract: Synthesis, characterization and biological activity of two new platinum complexes is described. One of those complexes showed inhibitory effects on six tumor cell lines. The activity was attributed to inhibition of two targets, DNA and thioredoxin reductase. Abstract: In the search of an effective chemotherapy for the treatment of cancer, in this work we describe the synthesis, characterization and biological activity of two new platinum complexes. The general formula is [Pt2 (L)(X)4 ], whereL was 1, 2, 4, 5-tetrakis((1 H- pyrazol-1-yl)methyl)benzene and X were iodine (1 ) and chlorine (2 ). The most probable structure was established through a combination of spectroscopic analysis and density functional theory (DFT) calculations. Studies of interaction of complexes with DNA were carried out, and the results by spectroscopic titrations, thermal denaturation and viscosity, showed noncovalent interactions of complexes with DNA. The comet assay showed damage to cellular DNA. Inhibition assays of thioredoxin reductase (TrxR) were carried out, and the compounds showed notable inhibitory activity on the enzyme in a concentration dependent manner, with IC50 values of 3.9 and 3.5 nM for1 and2 respectively. Complex2 exhibited greater inhibitory effects than complex1 against all the tumor cell lines, with growth inhibitory effects superior to cisplatin in some cases.